2011
DOI: 10.1111/j.1463-1326.2011.01538.x
|View full text |Cite
|
Sign up to set email alerts
|

Controversies surrounding the clinical potential of cinnamon for the management of diabetes

Abstract: Obesity levels have increased significantly in the past five decades and are predicted to continue rising, resulting in important health implications. In particular, this has translated to an increase in the occurrence of type II diabetes mellitus (T2D). To alleviate associated problems, certain nutraceuticals have been considered as potential adjuncts or alternatives to conventional prescription drugs. Cinnamon, a commonly consumed spice originating from South East Asia, is currently being investigated as a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
57
0
4

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(64 citation statements)
references
References 50 publications
1
57
0
4
Order By: Relevance
“…Cinnamon has traditionally been used for rheumatism, wounds, diarrhea, headaches, and colds [136]. Recently, extensive studies have been performed on the action of cinnamon on diabetes and metabolic syndrome [135].…”
Section: Selected Medicinal Herbs and Compounds For T2dmentioning
confidence: 99%
“…Cinnamon has traditionally been used for rheumatism, wounds, diarrhea, headaches, and colds [136]. Recently, extensive studies have been performed on the action of cinnamon on diabetes and metabolic syndrome [135].…”
Section: Selected Medicinal Herbs and Compounds For T2dmentioning
confidence: 99%
“…The controversy regarding effects of cinnamon undoubtedly exists and further studies required determining the patient population which could benefit from cinnamon supplementation. Detailed review of findings regarding cinnamon interventions in diabetes mellitus can be found in other papers (35, 36). …”
Section: Dietary and Topical Interventions In Obese And Diabetic Condmentioning
confidence: 99%
“…For example, some studies reported that cinnamon supplementation did not have any significant effects on type 2 diabetic patients [9,10] . Cinnamon is produced from the bark of multiple species of Cinnamomum, which contains a variety of compounds, such as cinnamaldehyde, eugenol, and polyphenols [11] . Recently, active water-soluble components were isolated and found to Trimer procyanidin oligomers contribute to the protective effects of cinnamon extracts on pancreatic β-cells in vitro 1084 www.nature.com/aps Sun P et al Acta Pharmacologica Sinica mediate beneficial effects on glucose metabolism [12][13][14] .…”
Section: Introductionmentioning
confidence: 99%